From the Horizontal Garden to the Vertical Garden: An Architectural and Environmental Perspective of the “Green” Element - Martins, Ana Maria Tavares (2020)
Throughout human history, gardens comprised many purposes. With the evolution of society, there were villages, towns and cities organized according to geographical, economic, social and cultural characteristics of each epoch. Throughout the history of mankind, the "green" element has always been present. Gardens accompanied this development depending on the theories in vogue and had several purposes: they were sacred spaces, leisure spaces or spaces of healing; they were architectural elements in the characterization of outdoor spaces; they were areas of experimentation and research. After the Industrial Revolution, urban areas have expanded dramatically, occupying large amounts of rural soil replacing natural vegetation with the modernist urban structure. At the end of the 19th century and beginning of the 20th century, the acquired garden concept had been challenged, stretching, instead, over a horizontal surface in the form of green roofs which characterized many of the modernist buildings. In fact, from the modernist movement on, horizontal covers, that lead to various experiments in the context of green roofs and garden which may be used and enjoyed by its inhabitants or covered and accessible only for maintenance purposes, have appeared. Through the end of the 20th century and early 21st century, the horizontal roof was then an experimental ground on which architecture could respond to a new challenge: the green facades or vertical gardens. In this way, the built environment can be the support for a new concept of green structure and urban or rural "green", i.e, a vertical garden: a green facade. This new "green skin" of the building can regulate the temperature and air quality as well as control the amount of light inside the building or be an aesthetic element of the architectural coating. New architectural elements are created through which adverse environmental conditions are mitigated, either on new construction or on architectural rehabilitation.